2020
DOI: 10.3390/tropicalmed5020072
|View full text |Cite
|
Sign up to set email alerts
|

Levels of 25-hydroxy Vitamin D3 and Vitamin D Receptor Polymorphism in Severe Dengue Cases from New Delhi

Abstract: Background: Dengue is the “phoenix” that never went to ashes. First identified in 1943, in Japan, dengue virus has worldwide distribution and is a grave public health concern in developing countries like India; Methods: A cross sectional study was conducted among adults suspected of having dengue fever and attending Lok Nayak Hospital, New Delhi. Restriction Fragment Length Polymorphism was completed for the detection of vitamin D receptor (VDR) gene polymorphism; Results: Serum 25-hydroxy vitamin D3 (vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“… State/ union territories Case/million Death/million Total no. of healthy subjects Mean 25(OH)D levels (ng/ml) References Andhra Pradesh 5530 50 1936 18 [32] , [33] , [34] , [35] , [36] Assam 2390 6 768 26 [37] , [38] , [39] Bihar 940 4 50 30 [40] Chandigarh 1830 27 878 34 [41] , [42] , [43] , [44] , [45] , [46] Delhi 8970 249 2919 15 [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] Goa 7520 64 …”
Section: Resultsmentioning
confidence: 99%
“… State/ union territories Case/million Death/million Total no. of healthy subjects Mean 25(OH)D levels (ng/ml) References Andhra Pradesh 5530 50 1936 18 [32] , [33] , [34] , [35] , [36] Assam 2390 6 768 26 [37] , [38] , [39] Bihar 940 4 50 30 [40] Chandigarh 1830 27 878 34 [41] , [42] , [43] , [44] , [45] , [46] Delhi 8970 249 2919 15 [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] Goa 7520 64 …”
Section: Resultsmentioning
confidence: 99%
“…However, in contrast to these studies, a study undertaken in Colombia showed that lower vitamin D levels were associated with decreased odds of progression of DF patients to DHF/DSS [ 58 ], while another study reported that vitamin D levels were higher in DF and DHF patients as compared to normal controls [ 59 ]. A third study on adults with non-severe or severe cases of dengue found vitamin D levels were elevated in both non-severe and severe cases as compared to healthy controls [ 60 ]. Thus, there remains no consensus on the association between vitamin D serostatus and either infection or severity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, while Alagarasu and colleagues [ 59 ] found a significantly lower frequency of the ‘C’ allele of the rs7975232 polymorphism in dengue patients as compared to healthy controls, Singh and colleagues [ 65 ] found the GG genotype at this position to be higher in patients than controls. However, both studies by Alagarasu and colleagues [ 59 ] and Chakravarti and colleagues [ 60 ] showed that the “T” allele at rs2228570 was associated with severe dengue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation